2017
DOI: 10.1016/j.ijheatmasstransfer.2016.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of heat transfer between thin liquid films flowing down a vertical string in the Rayleigh-Plateau instability regime and a counterflowing gas stream

Abstract: Direct contact heat exchangers based on wetted string columns offer an intriguing alternative to packed beds and spray columns. We experimentally examine the flow and heat transfer characteristics of thin liquid films flowing down strings of a diameter approximately 1 mm against a counterflowing air stream. Numerical simulations are also performed to help interpret and validate our experimental results. The Rayleigh-Plateau instability caused by interplay among surface tension, gravity, and viscous forces lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…A previous study by Nozaki et al [7] and our numerical simulation study [34] indicated that spatial temperature variations within a liquid bead is less than 2% of the bead mean temperature. At measurement locations, secondary flows generated by interactions with the micro-thermocouples are expected to further…”
Section: Fig 4 the Geometric Parameters Of The Travelling Beadsmentioning
confidence: 45%
See 2 more Smart Citations
“…A previous study by Nozaki et al [7] and our numerical simulation study [34] indicated that spatial temperature variations within a liquid bead is less than 2% of the bead mean temperature. At measurement locations, secondary flows generated by interactions with the micro-thermocouples are expected to further…”
Section: Fig 4 the Geometric Parameters Of The Travelling Beadsmentioning
confidence: 45%
“…The actual liquid-side heat transfer coefficient would be higher than this value because internal circulation within each bead enhances heat transfer [33]. Note that, for a fixed nozzle diameter, liquid films flowing in the Rayleigh-Plateau regime at different flow rates produce liquid beads of approximately the same radii but different inter-bead spacings [21,34].…”
Section: Heat Transfer Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In industrial applications, the coating processes may be operated in more complex environments and it is highly desirable to control the stability of the film by technological attempts. Recent and ongoing theoretical and experiment studies concentrate on the coating flows with thermocapillarity [14], in contact with current gas flow [15,16], flowing over a slippery surface [17]. When the coating flow is electrified by a concentric outer electrode, both the linear stability characteristics and nonlinear dynamics are altered.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the liquid is forced to run on defined flow paths and no radial flow occurs that could lead to maldistribution. Many researches have been done to study the interphase mass or heat transfer for such wetted‐wire when applied in gas separation . Grunig et al used the watch chain, armor chain, bead chain and locking wire to improve the liquid flow pattern on the surface of the wire.…”
Section: Introductionmentioning
confidence: 99%